Studies on the morphology, properties and biocompatibility of aliphatic diisocyanate-polycarbonate polyurethanes. (December 2015) - Fernández-d'Arlas, Borja; Alonso-Varona, Ana; Palomares, Teodoro; Corcuera, M Angeles; Eceiza, Arantxa
Abstract: Here it is addressed the results on the preparation of a novel set of biocompatible thermoplastic polyurethane (PU) elastomers. The main purpose of this work was to study the nano/microstructure obtained when substituting commonly used aromatic diisocyanates, such as 4, 4′-methylene diphenyl diisocyanate (MDI) by the more biocompatible and also more crystalline aliphatic 1, 6-hexamethylene diisocyanate (HDI). The work aims to relate its physico-chemical characteristics with macroscopic properties such as hydrophobicity, thermal characteristics, mechanical properties, biodegradability and biocompatibility. Substitution of MDI by HDI developed more phase segregated materials with higher surface tension, allowing minimization of diisocyanate content into the PU for achieving the optimal biocompatible range. The polycarbonate blocks provide biostability over a period of 2 years. In addition, these materials were not cytotoxic and revealed good adhesion of the cells, assessed by SEM, suggesting that they may be valid candidates for biomedical use.